The Listeria monocytogenes ChiA Chitinase Enhances Virulence through Suppression of Host Innate Immunity - Swarnava Chaudhuri; Benjamin N. Gantner; Richard D. Ye; Nicholas P. Cianciotto; Nancy E. Freitag (mBio, 2013)
ABSTRACT Environmental pathogens survive and replicate within the outside environment while maintaining the capacity to infect mammalian hosts. For some microorganisms, mammalian infection may be a relatively rare event. Understanding how environmental pathogens retain their ability to cause disease may provide insight into environmental reservoirs of disease and emerging infections. Listeria monocytogenes survives as a saprophyte in soil but is capable of causing serious invasive disease in susceptible individuals. The bacterium secretes virulence factors that promote cell invasion, bacterial replication, and cell-to-cell spread. Recently, an L. monocytogenes chitinase (ChiA) was shown to enhance bacterial infection in mice. Given that mammals do not synthesize chitin, the function of ChiA within infected animals was not clear. Here we have demonstrated that ChiA enhances L. monocytogenes survival in vivo through the suppression of host innate immunity. L. monocytogenes ΔchiA mutants were fully capable of establishing bacterial replication within target organs during the first 48 h of infection. By 72 to 96 h postinfection, however, numbers of ΔchiA bacteria diminished, indicative of an effective immune response to contain infection. The ΔchiA-associated virulence defect could be complemented in trans by wild-type L. monocytogenes, suggesting that secreted ChiA altered a target that resulted in a more permissive host environment for bacterial replication. ChiA secretion resulted in a dramatic decrease in inducible nitric oxide synthase (iNOS) expression, and ΔchiA mutant virulence was restored in NOS2−/− mice lacking iNOS. This work is the first to demonstrate modulation of a specific host innate immune response by a bacterial chitinase. IMPORTANCE Bacterial chitinases have traditionally been viewed as enzymes that either hydrolyze chitin as a food source or serve as a defense mechanism against organisms containing structural chitin (such as fungi). Recent evidence indicates that bacterial chitinases and chitin-binding proteins contribute to pathogenesis, primarily via bacterial adherence to chitin-like molecules present on the surface of mammalian cells. In contrast, mammalian chitinases have been linked to immunity via inflammatory immune responses that occur outside the context of infection, and since mammals do not produce chitin, the targets of these mammalian chitinases have remained elusive. This work demonstrates that a Listeria monocytogenes-secreted chitinase has distinct functional roles that include chitin hydrolysis and suppression of host innate immunity. The established link between chitinase and the inhibition of host inducible nitric oxide synthase (iNOS) expression may help clarify the thus far elusive relationship observed between mammalian chitinase enzymes and host inflammatory responses occurring in the absence of infection.